Safety of hospital discharge before return of bowel function after elective colorectal surgery. Issue 5 (24th January 2020) - ,
Abstract : Background: Ileus is common after colorectal surgery and is associated with an increased risk of postoperative complications. Identifying features of normal bowel recovery and the appropriateness for hospital discharge is challenging. This study explored the safety of hospital discharge before the return of bowel function. Methods: A prospective, multicentre cohort study was undertaken across an international collaborative network. Adult patients undergoing elective colorectal resection between January and April 2018 were included. The main outcome of interest was readmission to hospital within 30 days of surgery. The impact of discharge timing according to the return of bowel function was explored using multivariable regression analysis. Other outcomes were postoperative complications within 30 days of surgery, measured using the Clavien–Dindo classification system. Results: A total of 3288 patients were included in the analysis, of whom 301 (9·2 per cent) were discharged before the return of bowel function. The median duration of hospital stay for patients discharged before and after return of bowel function was 5 (i.q.r. 4–7) and 7 (6–8) days respectively ( P < 0·001). There were no significant differences in rates of readmission between these groups (6·6 versus 8·0 per cent; P = 0·499), and this remained the case after multivariable adjustment for baseline differences (odds ratio 0·90, 95 per cent c.i. 0·55 to 1·46; P = 0·659). Rates of postoperative complications were also similar in those discharged before versus after return of bowel function (minor: 34·7 versus 39·5 per cent; major 3·3 versus 3·4 per cent; P = 0·110). Conclusion: Discharge before return of bowel function after elective colorectal surgery appears to be safe in appropriately selected patients. Abstract : This study explored the safety of hospital discharge before return of bowel function. The study was performed across an international setting by a trainee‐ and student‐led collaborative group. Discharge before return of bowel function after elective colorectal surgery appeared to be safe in appropriately selected patients. No need to wait Abstract : Antecedentes: El íleo es frecuente tras la cirugía colorrectal y se asocia con un aumento del riesgo de las complicaciones postoperatorias. Identificar las características de una recuperación normal del tránsito y la idoneidad para el alta hospitalaria es una tarea difícil. Este estudio examinó la seguridad del alta hospitalaria antes del restablecimiento de la función intestinal. Métodos: Se llevó a cabo un estudio de cohortes prospectivo y multicéntrico a través de una red de colaboración internacional. Se incluyeron pacientes adultos sometidos a resección electiva colorrectal entre enero y abril 2018. El objetivo principal fue el reingreso hospitalario durante los 30 primeros días tras la intervención. Se utilizó un análisis de regresión multivariable para evaluar el impacto del momento del alta en función del restablecimiento de la función intestinal. El objetivo secundario fue las complicaciones postoperatorias en los primeros 30 días después de la cirugía, valoradas mediante el sistema de clasificación de Clavien‐Dindo. Resultados: Se incluyeron en el análisis 3.288 pacientes, de los cuales 301 (9, 2%) fueron dados de alta antes del restablecimiento de la función intestinal. La mediana de la estancia hospitalaria de los pacientes dados de alta antes y después del restablecimiento de la función intestinal fue 5 (rango intercuartílico: 4‐7) y 7 (6‐8) días, respectivamente ( P < 0, 001). No hubo diferencias significativas en las tasas de reingreso entre estos grupos (6, 6% versus 8, 0%; P = 0, 499), y este resultado se mantuvo en el análisis multivariable tras el ajuste por diferencias basales (razón de opotunidades, odds ratio, OR 0, 90; i.c. del 95% 0, 55‐1, 46, P = 0, 659). Las tasas de complicaciones postoperarorias fueron similares en aquellos dados de alta antes o después del restablecimiento de la función intestinal (complicaciones menores: 34, 7% versus 39, 5%; complicaciones mayores 3, 3% versus 3, 4%; P = 0, 110). Conclusión: Dar de alta antes del restablecimiento de la función intestinal tras cirugía colorrectal electiva parece ser seguro en pacientes debidamente seleccionados.